Acute Stanford type A aortic dissection associated with aortic coarctation repaired by Tirone E. David & debranching techniques with combined axillar and femoral perfusion: a case report - Guerrero, Francisco (2021)
We present the case of a 38-year-old male with a diagnosis of Stanford A aortic dissection and associated coarctation of the thoracic aorta. Acute dissection associated with coarctation of the aorta is a rare problem and difficult to manage surgically. Establishing a cardiopulmonary bypass (CPB) with adequate flows is the main objective of the procedure; optimal cannulation ensures the protection of cerebral and visceral organs. We successfully performed aortic valve re-implantation surgery (T. David Surgery), replacement of the ascending aorta and aortic arch, as well as debranching of the supra-aortic trunks. The cannulation technique was axillary and femoral to guarantee flows through the coarctation area.